Tracer study alumni Program Studi Tata Boga Politeknik Negeri Balikpapan - Rofi'ah, Novi Ulfatur; Ulum, Miftahul; Wijadmoko, Wijadmoko (Borneo Novelty Publishing, 2025)
Abstract The Culinary Study Program is one of the departments at the Balikpapan State Polytechnic and the only one in the city of Balikpapan, specializing in providing skilled workforce in the culinary field. To gather information about the transition and career history of graduates, conducting a tracer study is essential. A tracer study is a follow-up study of alumni to track their movement in the job market, typically conducted at least one year after graduation. The purpose of this research is to determine the profile of alumni from the Culinary Study Program at the Balikpapan State Polytechnic for the years 2021 to 2023, based on their employment status, and to assess the employers' evaluation of these alumni. This study is a descriptive quantitative research using a survey approach. The tracked alumni totaled 138 individuals, while 68 employers were surveyed. The results show that 61% of alumni are employed, with a waiting period of 1-3 months for most alumni. The highest percentage of alumni work in multilateral institutions or organizations. Most alumni earn above the regional minimum wage (UMK), and the alumni of the Culinary Arts Study Program have received positive evaluations in various assessment aspects.